Counseling and Education on Diet for Communities During the Covid-19 Pandemic in Banda Aceh - Husnah, Husnah; Syadza, Sausan; Ramadhan, Muhammad Haris; Sakdiah, Sakdiah (Media Ilmu Keolahragaan Indonesia, 2021)
Counseling and education about Covid-19 to the public is important, especially the mode of transmission, clinical symptoms, severity of disease and prevention efforts as well as how to increase body immunity through healthy eating patterns and vaccinations. The need for macronutrient and micronutrient nutrients and fluids can increase the body#39;s immune system which plays a role in fighting Covid-19 infection. Dietary education to the public is a reference for daily nutritional needs and nutritional therapy for Covid-19 patients. Enteral or parenteral nutritional formulas can be recommended for consumption. Infectious diseases increase the risk of malnutrition. In the case of Covid-19, there is an increase in energy requirements due to increased work of the respiratory muscles, fever, cough, and mechanical ventilation. The purpose of the study was to determine the relationship between knowledge, community behavior and eating patterns during the Covid-19 pandemic and to provide counseling on Covid-19 preventive efforts. Collecting data by non-probability sampling purposive technique from 15 to 30 September 2020 at 8 Integrated Healthcare Center in Banda Aceh, with a total sample of 664 respondents. The type of research is observational analytic cross sectional design. The results of the study were that the dominant age was over 60 years as many as 261 respondents (39.3%), the most gender was female 464 respondents (69.9%), housewife work was 252 people (38%), the most comorbid diseases were hypertension 235 people (35.4%), Diabetes mellitus 219 people (33%). Good knowledge about Covid-19 was 564 respondents (82.2%), correct behavior was 493 people (74.2%) and correct eating patterns were 400 respondents (74.2%). There is a relationship between knowledge and behavior during the Covid-19 pandemic (P value = 0.000) and there is a relationship between knowledge and diet (P value = 0.039). It was concluded that knowledge affects people#39;s behavior and eating patterns during the Covid-19 pandemic.